2015
DOI: 10.1210/jc.2014-3754
|View full text |Cite
|
Sign up to set email alerts
|

Evening Chronotype Is Associated With Metabolic Disorders and Body Composition in Middle-Aged Adults

Abstract: At the population level, evening chronotype was independently associated with diabetes, metabolic syndrome, and sarcopenia. These results support the importance of circadian rhythms in metabolic regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
205
7
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(238 citation statements)
references
References 46 publications
18
205
7
8
Order By: Relevance
“…As sleep–wake timing and diurnal preference have been associated with individual differences in sleep quality,49 metabolism,50 and mental health,51 we also assessed this aspect of sleep. PC1 component explained 34% of the variation across all studied measures within this domain (see Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…As sleep–wake timing and diurnal preference have been associated with individual differences in sleep quality,49 metabolism,50 and mental health,51 we also assessed this aspect of sleep. PC1 component explained 34% of the variation across all studied measures within this domain (see Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The shiftworkers in the UK Biobank were more likely to report an evening preference, which may be important as this phenotype is associated with susceptibility to metabolic disease including increased BMI, [33][34][35] metabolic syndrome, [33] type 2 diabetes and hypertension, [35] as well as all-cause mortality, [36] and might contribute to the increased prevalence of metabolic disease in shiftworkers.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 A direct relationship between circadian rhythm disruption and skeletal muscle disease has not been identified in humans. However, several basic studies of different mouse models of clock gene deficiency have found that molecular clock disruption affects skeletal muscle physiology.…”
Section: Resultsmentioning
confidence: 99%
“…However, Yu et al recently found that the prevalence of diabetes, metabolic syndrome, and sarcopenia is 8.2%, 7.4%, and 6.7% higher, respectively, in individuals classified as having an evening, rather than a morning, chronotype among middle-aged Korean population, although the average age was lower in individuals with an evening, rather than a morning, chronotype. 2 Although submit your manuscript | www.dovepress.com…”
Section: Introductionmentioning
confidence: 99%